Effects of an artistic gymnastics program on the hyperactivity index in schoolchildren aged 6 to 11 years with a diagnosis of ADHD. (Revista horizonte, 2014)
The objective of this research was to analyze the effects of a program of artistic gymnastics in the index of children with a diagnosis of ADHD. Under a design studied quasi experimental, descriptive and comparative data from a quantitative methodology. The sample was selected under a criterion not probabilistic whereas 60 children from 6 to 11 years divided into three groups of 20 agreements to children with ADHD diagnosis and application of gymnastics program, hyperactive without gymnastics program and children without hyperactivity or as group gymnastics program control. There were included regular students of the Colegio Adventista from the city of Antofagasta of Chile after signing an informed consent from parents and proceeding according to the Declaration of Helsinke, excluding those children who had voluntary retirement of research. Motor development scale (MDS) of pink net scale was used for the obtaining of motor development. The results show significant differences (p < 0.05) in the motor development of the three group in motor thin, global mobility, balance, body schema, temporal, and spatial organization, significant differences effects (p < 0.05) of artistic gymnastics in the motor development of children with hyperactivity. In conclusion, the implementation of a program of artistic gymnastics could be considered a useful tool in the approach to disorders of motor development in children with hyperactivity.